Perilaku Kepatuhan Diet Dan Aktivitas Fisik Terhadap Pengendalian Kadar Gula Darah Pasien Diabetes Mellitus Tipe Ii - Nonce Nova Legi; Ana B Montol; Grace K.L. Langi; Selvian Soflanit (POLTEKKES KEMENKES MANADO, 2018)
Diabetes Mellitus is a disorder of metabolism of carbohydrates, proteins and fats resulting from an imbalance between the availability of insulin and insulin requirements. se of this study was to determine the relationship of diet adherence and physical activity with controlling blood sugar levels in patients with type II diabetes mellitus outpatient at the Manado Radiation Hospital. This study was an observational analytic study with a cross sectional design. The population in this study were all Diabetes Mellitus Type II outpatients in the hospital. Pancaran Kasih Manado The number and sample are 39 people and the sample is determined by purposive sampling. The test results between the relationship of diet adherence with blood sugar levels obtained a p-value of 0.670, meaning that there was no significant relationship between the variables of diet compliance with blood sugar levels. While physical activity with blood sugar levels get a p-value of 0.499, it means there is no significant relationship between physical activity variables with blood sugar levels. The conclusion of this study is that there is no significant relationship between adherence to diet, physical activity with controlling blood sugar levels in patients with type 2 Diabetes Mellitus in the hospital Radiation of Love Manado.